Perancangan Sistem Informasi Booking Driver Berbasis Website pada Newman Bali Tour Menggunakan Metode Prototype - I Gede Prana Yoga; Ni Made Satvika Iswari; I Nyoman Purnama (Lembaga Pengembangan Kinerja Dosen, 2025)
Newman Bali Tour, a community of freelance drivers in Bali, faces conventional operational challenges such as irregular passenger distribution, uncertain driver availability, and a lack of price transparency. To address these issues, this research aims to design a website-based ordering information system to improve operational effectiveness and efficiency. This system will integrate features for automatic and equitable passenger distribution based on driver availability, as well as clear price transparency. The prototype method is used in the system design, encompassing the stages of: communication (interviews), quick planning (gathering interview results and necessary data), quick design (designing UML diagrams), prototype construction, and delivery and feedback (system testing using the System Usability Scale/SUS). System testing on 20 respondents yielded an average SUS score of 78, which falls into the